Monitoring and Evaluating Social Learning: A Framework for Cross-Initiative Application - Epp, Marissa van; Garside, Ben (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The Climate Change and Social Learning Initiative is a cross-organisation group working to build a body of evidence on how social learning methodologies and approaches contribute towards development targets. Together with a select number of participating initiatives from a variety of organisations, we are working towards establishing a common monitoring and evaluation (M&E) framework for new projects and programmes using a social learning-oriented approach. The aim is to more systematically collect evidence, analyse results and share learning on when and how research initiatives and beneficiaries may benefit from a social learning-oriented approach in the context of climate change adaptation and food security. This working paper presents an M&E framework consisting of a theory of change and 30 primary indicators across four key areas: iterative learning, capacity development, engagement, and challenging institutions. This framework will be accompanied by a forthcoming implementation guide for participating initiatives, as well as a strategy for peer assist, data collection and analysis by the CCSL Initiative.